Areas of Interdisciplinary Studies in Historical Context - Shykyrynska, Olha (Journal of Danubian Studies and Research, 2023)
The article deals with the historical development and functioning of the interdisciplinary studios. The scientists’ discoveries of the definition of the concept “synthesis of the arts” are analysed, beginning with the archaic period to today. The appearance and evolution of the term “intermedial theory” are represented in this work. The research is based on the works of Sharl Batteux, Ivan Franko, Oskar Walzel, Steven Paul Scher, Oswald Spengler, Werner Wolf, Jens Schröter and others.